Socioeconomic Perspective and Analysis of the Linkage of Education and Child Labor in Pakistan: Challenges and Prospects - Muhammad Noaman Yousaf; Dr. Alamgir Khan; Umar Hayat; Awais Ahmad (Journal of Religion and Society, 2025)
This study examines the complex socioeconomic linkage between education and child labor in Pakistan, highlighting the persistent challenges and potential strategies for reform. Despite constitutional guarantees for free primary education, Pakistan remains one of the world's top countries for child labor, with economic deprivation, cultural norms, and systemic inequalities driving children into exploitative work environments. The paper argues that child labor not only deprives children of educational opportunities but also perpetuates intergenerational poverty, undermining national economic growth and social cohesion. Drawing on theoretical frameworks such as human capital theory and conflict theory, the study identifies key barriers, including patriarchal structures, caste-based discrimination, and inadequate educational infrastructure, which discourage school enrollment. The analysis reveals that families often prioritize immediate economic gains from child labor over long-term educational benefits, exacerbated by poor-quality schooling and societal attitudes. However, the study also outlines prospects for change, emphasizing the need for integrated policy interventions. Recommendations include financial incentives for education (e.g., scholarships), vocational training programs, and community awareness campaigns to shift perceptions about child labor. The paper stresses the importance of legal reforms, increased education budgets, and collaboration with NGOs to address root causes. By aligning Pakistan's youth bulge with future labor market demands through education and skill development, the study advocates for a holistic approach to break the cycle of poverty and exploitation. Ultimately, it calls for urgent action from policymakers, civil society, and international stakeholders to ensure equitable access to education and safeguard children's rights. Keywords: Child Labor, Education, Socioeconomic Barriers, Pakistan, Policy Reform, Poverty Cycle